Variability in phomopsis blight pathogen [Phomopsis vexans (Sacc. & Syd.) Harter] - and H.S. CHAUBE, JAMEEL AKHTAR* (Indian Phytopathology, 2006)
Variability study revealed significant and substantial differences in radial growth of the isolates on PDA. Similarly biomass production ranged between 20.0 mg to 353.0 mg. The morphological characters notably type of colony, colour, texture, zonation too differed significantly. The variation in stylospore morphology was relatively higher. The germinability of pycnidiospore from different isolates differed significantly and it ranged from 31.0 to 72.0 %. Except for isolates Pv 36 where conidial germination was bipolar too, in rest of the isolates the germination was unipolar. The germtube length and time taken for germination also differed significantly. The extent and magnitude of pycnidial development was variable. Pycnidia were black in some isolates while in some brown pycnidia developed. Pathogeecity revealed isolate Pv 36 as most aggressive isolate while isolate Pv 11 as least aggressive.